Pelaksanaan Penilaian Sikap Spiritual dalam Pembelajaran Daring: Studi di MIN 46 Aceh Besar - Cecep Farhani; Tria Marvida; Deni Indrawan (SAP (Susunan Artikel Pendidikan), 2022)
The impact of the corona virus turned out has affected many fields as happened in Indonesia including the economic, social, tourism and education fields. During the pandemic, online learning is now practiced in almost all parts of the world. Nowadays, as teachers, students don't meet in person, so it must be difficult to measure their attitude. A flexible option is to share the form online. The type of research used is a qualitative case study approach. The method used to collect survey data is observation and interviews. The data analysis method for this study uses the Miles and Huberman model. From the research results, it is known that during online learning, MIN 46 Aceh Besar teachers only use two attitude assessment techniques, namely observation and self-assessment using Google Forms.